Pola kepemimpinan kepala madrasah dalam meningkatkan mutu pendidikan di Madrasah Aliyah Negeri (MAN) Kebumen 2 - Mohamad Faozi (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This study aims to: 1) Describe the leadership of Principal MAN Kebumen 2 in improving teacher performance. 2) Describe the factors that support and impede efforts to improve the quality of education in MAN Kebumen 2. This research was conducted in MAN Kebumen 2. The research was a qualitative phenomenological design. The phenomenological approach aimed to understand the phenomena that occur in the study subjects, where the researcher described research results in the form of words acquired during the observations and interviews with informed. By using this verstehen method, a researcher could understand the concepts, perspectives, values, ideas, and norms prevailing in the madrassa, so there was no misinterpretation of the meaning of the object studied. In this study, data was designed using the approach in-depth interviews, observation, and documentation. Data collection methods that researchers used in this study were: 1) Interview, 2) Observation, 3) Documentation. The data was analyzed by series a reduction, display, verification. The results of the study show: 1) Leadership of Principal MAN Kebumen 2 in improving teacher performance by implementing a quality learning program to, determine the extent to which students absorb the material that has been submitted by teachers, for teachers professional improvement programs through workshops, training, seminars and training related with the development and education reform. 2) Principal Leadership of MAN Kebumen 2 in improving the Quality of Education in the implementation of all policies relating to the rules always consult with Madrasah Committee and Teacher, establish good relationships with subordinates, making it easier to identify the characteristics of each personnel, application of modern management to develop a vision and Madrasah mission through planning budgeting, program management, and monitoring well /monitoring program is run in accordance with the program or not, promoting transparency, openness Madrasah fund management and willing to accept the proposal suggestions from subordinates. A leader should always give a good example to his subordinates.